Kairo, Ägypten. Die koptischen Stelen des Deir Anba Hadra im Koptischen Museum. Die Arbeiten des Jahres 2017 - Krastel, Lena (e-Forschungsberichte des DAI, 2017)
The monastery of Anba Hadra on the west bank of the Nile opposite of modern Aswan is one of the best-preserved monasteries in Egypt. During its excavation in the late 19th and early 20th centuries, more than 140 funerary stelae were found in the debris of the monastic church. Even though all inscriptions of the stelae were published by H. Munier in 1930/31, there is hardly any information about the stelae themselves. Furthermore, current research on the Coptic written evidence of Deir Anba Hadra encourages a reinvestigation of the stelae. Therefore, a comprehensive documentation of the stelae kept in the Coptic Museum in Cairo was begun in 2017.